Estado y representación política en Brasil - Helcimara De Souza Telles (Les Cahiers ALHIM)
This article intends to focus on the relationship between the State and political representation in Brazil. In general, there is a tendency to analyze the party system simply as a result of the social forces acting upon the State. Differently from these usual approaches, the proposal presented here is based on the idea that the obstacles faced by Brazilian parties may have originated from the concentration of decision power in the hands of the State or the Executive branch. The difficulty faced by the political parties in taking root amidst society may have been caused by the strategic role played by the federal government, which generated the supremacy of the Executive branch over the Legislative, which in turn allowed the State’s permeability to private interests. The Brazilian parties are currently viewed as lacking discipline and representativeness. This article attempts to identify if the conditions in which the parties were created and developed molded these parties : can the conditions of the Brazilian society at the time when the parties were created explain their relationship with the State and government and the fragility of their representation? How does the formation of the State affect representation?